2010
DOI: 10.1155/2010/360136
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Uveal Melanoma and Cutaneous Melanoma: Two of a Kind?

Abstract: Cutaneous melanoma and uveal melanoma both derive from melanocytes but show remarkable differences in tumorigenesis, mode of metastatic spread, genetic alterations, and therapeutic response. In this review we discuss the differences and similarities along with the genetic research techniques available and the contribution to our current understanding of melanoma. The several chromosomal aberrations already identified prove to be very strong predictors of decreased survival in CM and UM patients. Especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 122 publications
(151 reference statements)
0
44
0
Order By: Relevance
“…Mutation of BRCA1-associated protein 1 (BAP1), located on chromosome 3p21, was frequently identified in metastatic UM [19][20][21] . Particularly, it was reported that BAP1 mutation in UM cells may cause the liver tropism [22] .…”
Section: Chromosomal and Genetic Abnormalitiesmentioning
confidence: 99%
“…Mutation of BRCA1-associated protein 1 (BAP1), located on chromosome 3p21, was frequently identified in metastatic UM [19][20][21] . Particularly, it was reported that BAP1 mutation in UM cells may cause the liver tropism [22] .…”
Section: Chromosomal and Genetic Abnormalitiesmentioning
confidence: 99%
“…23 However, these 2 tumors show remarkable differences in their metastatic spread and therapeutic response. 38,39 The same applies to their associated genetic findings: more than 80% of uveal melanomas carry mutations in GNA11 or GNAQ; in cutaneous melanoma, oncogenic mutations in BRAF and NRAS seem to be primarily involved. 15,40,41 However, both GNAQ/GNA11 and BRAF/NRAS activate a common pathway, the mitogen-activated protein kinase (MAPK).…”
Section: Study Populationmentioning
confidence: 99%
“…Nowadays the clinical treatment of uveal melanoma is mainly surgery and radiotherapy, systemic chemotherapy is only used in some advanced cases with metastasis. 1 Here we choose the combination of chemotherapy rather than radiotherapy and adenovirus is intended to explore a new way of topical chemotherapy plus topical injection of oncolytic virus to treat uveal melanoma. Next, some studies of the described combination treatment for other tumor type observed an augmentation of apoptosis [12][13][14][15] while our investigation demonstrated that whether monotherapy of DTIC or H101, or co-treatment appears to be related to cell cycle blocking instead of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Survival rates for UM remain poor due to the high frequency of metastases exhibiting significant resistance to systemic therapy, with median survival less than 6 months. 2 It is well-established that the primary goal of treating UM is to prevent metastases and save lives, followed secondarily by reserving the eyeball and vision.…”
Section: Introductionmentioning
confidence: 99%